The degree of application of logical thinking skills in classroom management by teachers in first-year schools in the city of Latakia - شيحا سماح; مهند مبيض (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
The aim of the current research is to determine the degree of application of logical thinking skills in classroom management by teachers in first-cycle schools in Lattakia Governorate according to the following variables (training courses, number of years of experience, and scientific and educational qualifications). In order to achieve the objectives of the research, the descriptive approach was used. By designing a scale consisting of four dimensions distributed over (30) items, the research sample included (128) male and female teachers in the first cycle schools in Latakia Governorate. Their performance in applying logical thinking skills in classroom management was evaluated by (23) mentors. Educationally, the research reached the following results: There are statistically significant differences between the average scores of the research sample members on the scale of applying logical thinking skills in classroom management according to the variable of training courses in the field of classroom management, in favor of teachers who have followed one or more training courses. There are no statistically significant differences between the average scores of the research sample members on the scale of applying logical thinking skills in classroom management according to the variable number of years of experience. There are statistically significant differences between the average scores of the research sample members on the scale of applying logical thinking skills in classroom management according to the academic and educational qualification variable, in favor of the higher qualification.